Design of Islamic Religious Education Curriculum and Learning Outcomes in the Implementation of the Merdeka Curriculum in Indonesia - Dina Bahriani Putri; Asiana Asiana; Novrian Eka Safutra; Abu Mansur; Baldi Anggara (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the design of the Islamic Religious Education curriculum and Learning Outcomes (Capaian Pembelajaran/CP) within the implementation of the Merdeka Curriculum in Indonesia. The implementation of the Merdeka Curriculum has introduced significant changes in the orientation of national education, particularly regarding competency-based learning, character development, and student-centered instruction. In the context of Islamic Religious Education, these changes influence curriculum structure, instructional approaches, and competency development across educational phases. This study employed a qualitative approach using a literature review design. Data were collected from policy documents, scientific journal articles, books, and relevant academic publications related to curriculum design, Islamic Religious Education, and the implementation of the Merdeka Curriculum. The collected data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that the Merdeka Curriculum has transformed Islamic Religious Education from content-oriented learning toward competency-based and contextual learning. The Learning Outcomes in Islamic Religious Education are systematically organized according to students’ developmental phases and integrate cognitive, affective, and psychomotor competencies. In addition, the curriculum emphasizes character education, critical thinking, social responsibility, and religious moderation through the integration of the Profil Pelajar Pancasila. The study concludes that the implementation of the Merdeka Curriculum strengthens the role of Islamic Religious Education as an instrument for competency development, character formation, and social transformation in contemporary Indonesian education.